Protein Tyrosine Phosphatase Non-receptor 22 Gene C1858T Polymorphism in Patients with Coexistent Type 2 Diabetes and Hashimoto's Thyroiditis - Bulut, Funda; Erol, Deniz; Elyas, Halit; Dogan, Halil; Ozdemir, Fethi Ahmet; Keskin, Lezan (Galenos Publ House, 2014)
Background: A protein tyrosine phosphatase non-receptor type 22 (PTPN22) C1858T gene polymorphism has been reported to be associated with both Type 2 diabetes mellitus (T2DM) and Hashimoto's thyroiditis (HT) separately. However, no study has been conducted to explore the C1858T polymorphism in T2DM and HT coexistent cases up to now. Aims: The study aimed to determine whether a relationship exists or not between the PTPN22 C1858T polymorphism and this coexistent patient group. Study Design: Case-control study. Methods: Peripheral blood samples from 135 T2DM patients, 102 patients with coexistent T2DM+HT, 71 HT patients and 135 healthy controls were collected into ethylenediaminetetraacetic acid (EDTA) anticoagulant tubes and genomic DNA was extracted. The PTPN22 C1858T polymorphism was analyzed using polymerase chain reaction (PCR) restriction fragment length polymorphism (RFLP) methods. Results: Statistically significant differences were not observed between the patient and control groups. This study demonstrated a statistically significant association between both the CT genotype and the T allele in the female patient group with coexistent T2DM+HT (CT genotype: p=0.04; T allele: p=0.045) with a statistically significant association between the CT genotype and the mean values of body mass index (BMI) and free T3 levels (FT3) (BMI: p=0.044 and FT3: p=0.021) that was detected in the patient group with coexistent T2DM+HT. The minor genotype TT was observed in none of the groups in this study. The CT genotype frequency was [number (frequency): 5 (3.8%), 7 (6.86%), 5 (7.04%), 3 (2.22%), while the T allele frequency was 5 (1.86%), 7 (3.44%), 5 (3.53%) and 3 (1.12%)] in the T2DM, T2DM+HT, HT and control groups, respectively. Conclusion: Our data suggest that the PTPN22 1858T allele and the CT genotype are associated with increased risk in female patients for coexistent T2DM+HT. The CT genotype was associated with high mean BMI and free T3 values in the patient group with coexistent T2DM+HT. These results demonstrate that T allele carriers were more often in the T2DM+HT group than in the T2DM group. Therefore, the combination of T2DM and HT with female gender may have higher T allele carriage in comparison to the T2DM only and male groups.
Keywords: Hashimoto's thyroiditis; polymorphism; protein tyrosine phosphatase non-receptor type 22; type 2 diabetes